How Egg Storage Duration Prior to Incubation Impairs Egg Quality and Chicken Embryonic Development: Contribution of Imaging Technologies - Adriaensen, Hans; Parasote, Vanille; Castilla, Ines; Bernardet, Nelly; Halgrain, Maeva; Lecompte, François; Réhault-Godbert, Sophie (Frontiers in Physiology, 2022)
Storing fertilised eggs prior to incubation is a frequent practice in commercial hatcheries to coordinate activities and synchronise hatchings. However, the conditions used to store eggs have major impacts on egg quality and the subsequent viability of chicken embryos. While storage temperatures of 16–18 °C are classically used in hatcheries, the duration of storage varies from three to more than ten days. We explored the effect of storage duration (zero, three or ten days; D0, D3 and D10, respectively) at 16 °C, 80% relative humidity (RH) on egg quality (Broiler, Ross 308), using computed tomography (CT) and classical measurements (egg weight, eggshell weight and strength, egg white pH, Haugh units, yolk index and colour). The results revealed that a storage duration of up to ten days negatively affected some egg quality traits (yolk index and volume, air chamber volume and egg white pH). Eggs stored for three or ten days were further incubated for 11, 13 or 15 days (37.8 °C, 55% RH). Eggs were analysed by magnetic resonance imaging (MRI) and CT to assess the development of the embryo and internal egg changes occurring during incubation. First, data showed that the fertility and sex ratio of eggs were not affected by storage duration. However, the mortality of viable eggs was increased in the D10 group compared to the D3 group. Results of non-invasive imaging technologies revealed that the storage of eggs for ten days impaired embryo growth as early as 11 days of incubation (decrease in brain and embryo volumes). Collectively, these data provide new evidence that the duration of egg storage negatively affects embryonic growth. They further corroborate that this parameter is likely to be crucial to synchronising embryonic stages and maybe reducing the hatching window, hence limiting the time spent by newborn chicks in hatchers. In addition, our results highlight that CT and MRI imaging technologies are useful non-invasive tools to evaluate egg quality prior to incubation and the impact of storage (or incubation) practices on developmental growth of the embryo.